The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s00210-023-02465-x
|View full text |Cite
|
Sign up to set email alerts
|

A year in pharmacology: new drugs approved by the US Food and Drug Administration in 2022

Abstract: While new drug approvals by the U.S. Food and Drug Administration (FDA) had remained stable or even increased in the first 2 years of the COVID-19 pandemic, the 37 newly approved drugs in 2022 are considerably less than the 53 and 50 new drugs approved in 2020 and 2021, respectively, and less than the rolling 10-year average of 43. As in previous years of this annual review, we assign these new drugs to one of three levels of innovation: first drug against a condition (“first-in-indication”), first drug using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 108 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…The number of novel drugs approved by the FDA in 2023 was similar to that in the past several years (Kayki-Mutlu and Michel 2021; Kayki-Mutlu et al 2022), except the pandemic-related dent observed in 2022 (Kayki-Mutlu et al 2023). The share of small molecules among new drug approvals has continuously declined in the past 4 years from 70% in 2020 to 49% in 2023.…”
Section: General Trends and Conclusionmentioning
confidence: 58%
See 3 more Smart Citations
“…The number of novel drugs approved by the FDA in 2023 was similar to that in the past several years (Kayki-Mutlu and Michel 2021; Kayki-Mutlu et al 2022), except the pandemic-related dent observed in 2022 (Kayki-Mutlu et al 2023). The share of small molecules among new drug approvals has continuously declined in the past 4 years from 70% in 2020 to 49% in 2023.…”
Section: General Trends and Conclusionmentioning
confidence: 58%
“…Our analyses follow the same protocol as those for newly approved drugs in 2020–2022 (Kayki-Mutlu and Michel 2021 ; Kayki-Mutlu et al 2022 , 2023 ) with one exception. Unlike in previous years, we have included cellular and gene therapies approved by the FDA (U.S. Food and Drug Administration 2023a , b ) into our analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations